Transport of 137Cs And 239,240Pu with Ice-rafted Debris in the Arctic Ocean - Landa, Edward R.; Reimnitz, Erk; Beals, Donna M.; Pochkowski, J.M.; Winn, Willard G.; Rigor, Ignatius (ARCTIC, 1998)
Ice rafting is the dominant mechanism responsible for the transport of fine-grained sediments from coastal zones to the deep Arctic Basin. Therefore, the drift of ice-rafted debris (IRD) could be a significant transport mechanism from the shelf to the deep basin for radionuclides originating from nuclear fuel cycle activities and released to coastal Arctic regions of the former Soviet Union. In this study, 28 samples of IRD collected from the Arctic ice pack during expeditions in 1989-95 were analyzed for 137Cs by gamma spectrometry and for 239Pu and 240Pu by thermal ionization mass spectrometry. 137Cs concentrations in the IRD ranged from less than 0.2 to 78 Bq/kg (dry weight basis). The two samples with the highest 137Cs concentrations were collected in the vicinity of Franz Josef Land, and their backward trajectories suggest origins in the Kara Sea. Among the lowest 137Cs values are seven measured on sediments entrained on the North American shelf in 1989 and 1995, and sampled on the shelf less than six months later. Concentrations of 239Pu + 240Pu ranged from about 0.02 to 1.8 Bq/kg. The two highest values came from samples collected in the central Canada Basin and near Spitsbergen; calculated backward trajectories suggest at least 14 years of circulation in the Canada Basin in the former case, and an origin near Severnaya Zemlya (at the Kara Sea/Laptev Sea boundary) in the latter case. While most of the IRD samples showed 240Pu/239Pu ratios near the mean global fallout value of 0.185, five of the samples had lower ratios, in the 0.119 to 0.166 range, indicative of mixtures of Pu from fallout and from the reprocessing of weapons-grade Pu. The backward trajectories of these five samples suggest origins in the Kara Sea or near Severnaya Zemlya. Le transport glaciel constitue le principal mécanisme responsable du transport des sédiments à grain fin depuis les zones côtières jusqu'à la fosse du bassin Arctique. La dérive des débris du transport glaciel pourrait constituer un important mécanisme de transport, ...